Atypical 'benign behaviour' of eyelid sebaceous carcinoma - Alves, S (2013)
Eyelid sebaceous carcinoma is a rare tumour with slow growth and it is one of the most aggressive malignancies of the eyelid. Death rate can reach 6%. The diagnosis is often delayed because it is confused with other periocular lesions. The authors describe a case with atypical presentation, regarding rapid growth rate and exophytic aspect. Female, 78 years, presenting lower eyelid tumour with 4 months of evolution. Ophthalmological examination showed a tarsal exophytic tumour (22 mm), non-adherent to bulbar conjunctiva. She was medicated topically for 3 months, with the diagnosis of chalazio. Total excision was performed for histological diagnosis. After diagnosis of sebaceous carcinoma with specific immunohistochemical markers, and without free tumour surgical limits, a second surgery was performed with a pentagon entire thickness excision. Being a rare tumour but with a considerable morbidity and mortality; early diagnosis and treatment is essential for a good prognosis and preservation of visual function.